Corticosteroid Biosynthesis Revisited: No Direct Hydroxylation of Pregnenolone by Steroid 21-Hydroxylase - Loke, Steffen; Stoll, Anna; Machalz, David; Botrè, Francesco; Wolber, Gerhard; Bureik, Matthias; Parr, Maria Kristina (Frontiers in Endocrinology, 2021)
Cytochrome P450s (CYPs) are an essential family of enzymes in the human body. They play a crucial role in metabolism, especially in human steroid biosynthesis. Reactions catalyzed by these enzymes are highly stereo- and regio-specific. Lack or severe malfunctions of CYPs can cause severe diseases and even shorten life. Hence, investigations on metabolic reactions and structural requirements of substrates are crucial to gain further knowledge on the relevance of different enzymes in the human body functionalities and origin of diseases. One key enzyme in the biosynthesis of gluco- and mineralocorticoids is CYP21A2, also known as steroid 21-hydroxylase. To investigate the steric and regional requirements of substrates for this enzyme, we performed whole-cell biotransformation assays with the fission yeast Schizosaccharomyces pombe recombinantly expressing CYP21A2. The progestogens progesterone, pregnenolone, and their 17α-derivatives were used as substrates. After incubation, samples were analyzed using gas chromatography coupled to mass spectrometry. For progesterone and 17α-progesterone, their corresponding 21-hydroxylated metabolites desoxycortone and cortodoxone were detected, while after incubation of pregnenolone and 17α-pregnenolone, no hydroxylated product was observed. Findings were confirmed with authentic reference material. Molecular docking experiments agree with these results and suggest that interaction between the 3-oxo group and arginine-234 of the enzyme is a strict requirement. The presented results demonstrate that the presence of an oxo-group in position 3 of the steroid is indispensable, where a 3-hydroxy group prevents hydroxylation in position C-21 by CYP21A2. This knowledge may be transferred to other CYP21A2 substrates and hence help to gain essential insights into steroid metabolism.